Teaching Pickleball with In-Depth Content Knowledge in Middle School Physical Education. Issue 8 (12th October 2020) - Kim, Insook; Oh, Daekyun; Kim, Mijoo; Cho, Kyuil
Abstract : This article describes specific components of each common content knowledge and specialized content knowledge within the pickleball context. In addition, it provides possible examples of each element aligning with the national grade-level outcomes associated with net games for 6–8th graders. This article allows teachers who are seeking meaningful and relevant resources for teaching pickleball to deepen understandings of the pickleball content, thereby giving their students opportunities for successful learning in physical education.